Commonwealth Caribbean Law of Trusts : Third edition. - Kodilinye, Gilbert (Taylor and Francis, 2014)
The law of trusts is a subject of growing importance in the Commonwealth Caribbean. Traditional areas, such as testamentary trusts, constructive trusts and charitable trusts, are now fully incorporated into the mainstream legal system, whilst newer types of trust, such as investment trusts and pension scheme trusts, are of increasing significance. This book has been updated to reflect important new case law and legislation.